Convergence of global and traditional managers’ characteristics: a case of senior management of cooperatives in Malaysia - Ismail, Yusof; Mhd. Sarif, Suhaimi (Inderscience Enterprises, 2010)
Senior management plays a very significant role to enhance the profitability of cooperatives. Unlike traditional companies, which are regulated by the Commission of Companies Malaysia, cooperatives are regulated by the Cooperative Commission of Malaysia. Malaysian cooperative managers may need to adjust to changing global business environment to remain competitive in the economy. This paper attempts to investigate the perceptions of cooperatives’ senior management towards managerial roles and global skills, and aggregate the two sets of dimensions into broader categories. Factor analysis of the responses from 133 cooperative managers surveyed suggests that Malaysian cooperative managers are expected to have three composite skills labelled as cultural adaptability, public relations, and human development.